Swimming against the current: Australian climate institutions and the politics of polarisation. (20th October 2021) - MacNeil, Robert
ABSTRACT: While a large body of scholarship has analysed the nature and dysfunction of Australian climate policy over the past generation, there has been little examination of how the Australian state has reorganised itself institutionally to create and execute climate policy. Filling this gap, I explore the evolution of federal climate institutions since the early 1990s, describing how they have fared in the midst of Australia's highly polarized political debate around climate, as well as how they have facilitated and constrained Canberra's ability to develop effective climate strategies.